Indian residents willingness to pay green cess to support electric mobility ecosystem: A societal benefit perspective - Prasanna G. Tillu; Abhijeet K. Digalwar (Societal Impacts)
This study investigates the societal benefit of willingness to pay (WTP) green cess on polluting vehicles, to build an ecosystem for promoting zero emissions electric mobility in Western India. A survey method employed enabled data collection from 492 commuters and analysed using an open-ended contingent valuation method (CVM). As per the findings, about 67 % of commuters are in favour to pay green cess to help building an ecosystem for faster adoption of electric vehicles, but at comparatively low price. On positive note, around acknowledged electric mobility adoption needs a supportive ecosystem, while were not so forthcoming. The findings depicted that the average open-ended WTP for green cess evaluates to Rs 370 per month. The study engages commuters as stakeholders, helps analyse their sustainability orientation in terms of WTP and suggests recommendations for utilizing key learnings and monetary tool for inclusive developments towards a cleaner environment.